A Multi-Domain Bivariate Approach for Mixed Convection in a Casson Nanofluid with Heat Generation - OYELAKIN, Ibukun Sarah; MONDAL, Sabyasachi; SIBANDA, Precious; MOTSA, Sandile Sydney (Walailak Journal of Science and Technology (WJST), 2018)
We study the mixed convection flow of a Casson nanofluid past a permeable moving flat plate with heat generation, chemical reaction and viscous dissipation effects in the presence of thermo and thermal diffusion effects. The fluid model described assumes the nanoparticle flux at the boundary is zero, and suction effects on the velocity boundary are accounted for. The system of partial differential equations obtained is solved using a multi-domain bivariate quasi-linearization method with a detailed description of the numerical method of solution. The effects of various fluid parameters on the velocity, temperature, and nanoparticle concentration profiles, as well as on the local skin friction, and heat and mass transfer coefficients, are discussed in detail.